Algebra
- If x = y + z then x³ – y³ – z³ is
-
View Hint View Answer Discuss in Forum
x = y + z ⇒ x – y – z = 0
If a + b + c = 0 then a³ + b³ + c³ = 3abc
∴ (x)³ + (–y)³ + (–z)³ = 3x (–y) (–z) = 3xyzCorrect Option: B
x = y + z ⇒ x – y – z = 0
If a + b + c = 0 then a³ + b³ + c³ = 3abc
∴ (x)³ + (–y)³ + (–z)³ = 3x (–y) (–z) = 3xyz
- If x = 11, the value of x5 – 12x4 + 12x³ – 12x² + 12x - 1 is
-
View Hint View Answer Discuss in Forum
x5 – 12x4 + 12x³ – 12x² + 12x – 1
= x5 – (11 + 1) x4 + (11 + 1)x³ – (11 + 1)x² + (11 + 1) x – 1
= x5 – 11x4 – x4 + 11x³ + x³ – 11x² – x² + 11x + x – 1
= x – 1 = 11 – 1 = 10
[∵ x = 11]Correct Option: B
x5 – 12x4 + 12x³ – 12x² + 12x – 1
= x5 – (11 + 1) x4 + (11 + 1)x³ – (11 + 1)x² + (11 + 1) x – 1
= x5 – 11x4 – x4 + 11x³ + x³ – 11x² – x² + 11x + x – 1
= x – 1 = 11 – 1 = 10
[∵ x = 11]
- If a = 101, then the value of a (a² – 3a + 3) is :
-
View Hint View Answer Discuss in Forum
a = 101 (Given)
∴ a (a² – 3a + 3)
= a³ – 3a² + 3a – 1 + 1
= (a – 1)³ + 1 = (100)³ + 1 = 1000001Correct Option: C
a = 101 (Given)
∴ a (a² – 3a + 3)
= a³ – 3a² + 3a – 1 + 1
= (a – 1)³ + 1 = (100)³ + 1 = 1000001
-
If a + 1 ² = 3, then the value of a³ + 1 is : a a³
-
View Hint View Answer Discuss in Forum
Given a + 1 ² = 3 a ⇒ a + 1 = √3 a
On cubing both sides,a + 1 ³ = (√3)³ a ⇒ a³ + 1 + 3 a + 1 = 3√3 a³ ⇒ a³ + 1 = 3√3 = 3√3 a³ ⇒ a³ + 1 = 3√3 - 3√3 = 0 a³
Correct Option: A
Given a + 1 ² = 3 a ⇒ a + 1 = √3 a
On cubing both sides,a + 1 ³ = (√3)³ a ⇒ a³ + 1 + 3 a + 1 = 3√3 a³ ⇒ a³ + 1 = 3√3 = 3√3 a³ ⇒ a³ + 1 = 3√3 - 3√3 = 0 a³
-
If a² + b² = b² + c² = c² + a² = 1 (k ≠ 0) then k = ? c² a² b² k
-
View Hint View Answer Discuss in Forum
a² + b² = b² + c² = c² + a² = 1 c² a² b² k
⇒ c² = k (a² + b²);
a² = k (b² + c²);
b² = k (c² + a²)
∴ a² + b² + c² = k (b² + c² + c² + a² + a² + b²)
⇒ a² + b² + c² = 2k (a² + b² + c²)
⇒ 2k = 1⇒ k = 1 2 Correct Option: D
a² + b² = b² + c² = c² + a² = 1 c² a² b² k
⇒ c² = k (a² + b²);
a² = k (b² + c²);
b² = k (c² + a²)
∴ a² + b² + c² = k (b² + c² + c² + a² + a² + b²)
⇒ a² + b² + c² = 2k (a² + b² + c²)
⇒ 2k = 1⇒ k = 1 2